UNDERSTANDING RELATIONSHIP INTELLECTUAL CAPITAL AND FINANCIAL PERFORMANCE ON HEALTHCARE SECTOR - Jovita , Jovita; Nuringsih, Kartika (Graduate Program of Universitas Tarumanagara, 2023)
In the era of knowledge-based economy, companies pay more attention to intellectual capital than managing tangible assets. This study aims to analyze the effect of the components of intellectual capital including human capital, structural capital, relational capital, and capital employed on the achievement of financial performance in the healthcare sector during the period intersecting with the pandemic. The sampling technique using purposive sampling obtained 15 companies during the 2019-2021 period so that the total observations were 45 firm-years. Quantitative research design using multiple regression with random effect model analysis. The results show that structural capital and capital employed have a significant positive effect of 5 percent on financial performance, while relational capital has the opposite effect. Human capital does not have a significant effect on achieving return on asset performance. As a post-pandemic implementation, the four components of intellectual capital should be managed in a balanced way so that they can add value to the sector.